Blockade of P‐Selectin Is Sufficient to Reduce MHC I Antibody‐Elicited Monocyte Recruitment In Vitro and In Vivo. Issue 2 (27th December 2012) - Valenzuela, N. M.; Hong, L.; Shen, X.‐Da; Gao, F.; Young, S. H.; Rozengurt, E.; Kupiec‐Weglinski, J. W.; Fishbein, M. C.; Reed, E. F.
Abstract : Donor‐specific HLA antibodies significantly lower allograft survival, but as yet there are no satisfactory therapies for prevention of antibody‐mediated rejection. Intracapillary macrophage infiltration is a hallmark of antibody‐mediated rejection, and macrophages are important in both acute and chronic rejection. The purpose of this study was to investigate the Fc‐independent effect of HLA I antibodies on endothelial cell activation, leading to monocyte recruitment. We used an in vitro model to assess monocyte binding to endothelial cells in response to HLA I antibodies. We confirmed our results in a mouse model of antibody‐mediated rejection, in which B6.RAG1 −/− recipients of BALB/c cardiac allografts were passively transferred with donor‐specific MHC I antibodies. Our findings demonstrate that HLA I antibodies rapidly increase intracellular calcium and endothelial presentation of P‐selectin, which supports monocyte binding. In the experimental model, donor‐specific MHC I antibodies significantly increased macrophage accumulation in the allograft. Concurrent administration of rPSGL‐1‐Ig abolished antibody‐induced monocyte infiltration in the allograft, but had little effect on antibody‐induced endothelial injury. Our data suggest that antagonism of P‐selectin may ameliorate accumulation of macrophages in the allograft during antibody‐mediated rejection. Abstract : The authors demonstrate that donor class I‐specific antibody elicits endothelial exocytosis and P‐selectindependent monocyte recruitment, and that the P‐selectin antagonist rPSGL‐1‐Ig curbs macrophage accumulation in a murine cardiac allograft in response to these antibodies.